Efficiency market hypothesis in an emerging market: does it really hold for Malaysia? - Soon, Siew-Voon; Baharumshah, Ahmad Zubaidi; Chan, Tze-Haw (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study revisits the efficient market hypothesis (EMH) with regard to the Kuala Lumpur Stock Exchange (KZSE) at the sectoral level. Based on Liu and Narayan’s (2011) GARCH-based unit-root with structural breaks test, the unit-root null is rejected for all except one sector. By contrast, models based on commonly used unit-root tests that ignore heteroskedastic and/or breaks tend to favour the EMH. We find that the half-life estimates based on the local-persistent model are short, with the majority of them taking less than six months to absorb half a shock. All in all, the indices examined are largely inconsistent with weak-form efficiency, which implies that the returns on equity portfolios are indeed predictable.